Redesigning Kerupuk Atom Packaging And Label Of Kube Jaya Abadi And Up2k Sawo Pengudang Village, Teluk Sebong Sub-District, Bintan District - Susinggih Wijana; Panji Deoranto; Abi Karami; Nia Amalia Saputra; Danniary Ismail Faronny (Journal of Innovation and Applied Technology, 2021)
The processing of fishery products in an effort to increase the economic sector is carried out by the Kelompok Usaha Bersama (Kube) Jaya Abadi and the Usaha Peningkatan Pendapatan Keluarga (UP2K) Sawo located in Pengudang Village, Teluk Sebong Sub-district, Bintan District. Through the Doktor Mengabdi program, the Doktor Mengabdi and Kuliah Kerja Nyata Tematik at Universitas Brawijaya offer packaging and label redesign to increase selling value to become a superior product that can penetrate a wider market. Activities carried out include from gathering information through interviews via telephone and text messages to providing training and counseling on packaging and product labels. The result of this activity is knowledge about increasing the selling value of products through packaging and labels, as well as assistance with various equipment along with printed packaging and labels.